Tin-filtered 100 kV ultra-low-dose CT of the paranasal sinus: Initial clinical results - Petritsch, Bernhard (PLoS One, 2019)
OBJECTIVES: To investigate the feasibility, diagnostic image quality and radiation dose of 3(rd) generation dual-source computed tomography (CT) using a tin-filtered 100 kV protocol in patients with suspected acute inflammatory sinus disease. METHODS: We retrospectively evaluated 109 consecutive patients who underwent CT (Siemens SOMATOM Force, Erlangen, Germany) of the paranasal sinus with a new tin-filtered scan-protocol (Sn100 kV; tube current 35 mAs) using iterative reconstruction. Two readers independently assessed subjective image quality using a five-point Likert scale (1 = excellent, 5 = non-diagnostic). Inter-observer agreement was calculated and expressed as percentage of agreement. Noise was determined for calculation of signal-to-noise-ratio (SNR). Effective radiation dose (ED) was calculated from the dose-length-product (DLP). RESULTS: All examinations showed diagnostic image quality regarding evaluation of inflammatory sinus disease. On average, subjective general image quality was rated moderate (= 3) with a percentage of agreement between the observers of 81%. The mean image noise was 14.3 HU. The calculated median SNR was 6.0 for intraorbital fat, and 3.6 for the vitreous body, respectively. The median DLP was 2.1 mGy*cm, resulting in a median ED of 0.012 mSv. CONCLUSIONS: Taking the study limitations into account, ultra-low-dose tin-filtered CT of the paranasal sinus at a tube voltage of 100 kV utilizing an iterative reconstruction algorithm provides for reliable exclusion of suspected acute inflammatory sinus disease in 100% of the cases.